CdS–MoS2 heterostructures on Mo substrates via in situ sulfurization for efficient photoelectrochemical hydrogen generation. Issue 71 (15th September 2017) - Zhu, Xianglin; Wang, Peng; Zhang, Qianqian; Wang, Zeyan; Liu, Yuanyuan; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Huang, Baibiao
Abstract : CdS–MoS2 photoelectrode with a double layers core shell structure was prepared on Mo substrate through using a simple electrodeposition and– in situ sulfurization method on Mo substrate. Abstract : A CdS–MoS2 photoelectrode with a double-layer core–shell structure was prepared using a simple electrodeposition– in situ sulfurization method on a Mo substrate. The photocatalytic activity of as-prepared electrodes was evaluated using a photoelectrochemical H2 -generation experiment. The photocurrent and photon–electron conversion efficiency of the CdS–MoS2 photoelectrode were nearly double those of a CdS photoanode prepared on FTO glass. The high activity of the CdS–MoS2 photoelectrode was due to the higher separation efficiency of carriers caused by the formed CdS–MoS2 Janus heterojunction structure, which made directional transmission and electron–hole separation possible. Our experiments show that, in addition to being a good co-catalyst in powder material for photocatalytic hydrogen production, MoS2 can also be used as an electron acceptor layer to enhance electron–hole separation.